REPRODUCTIVE POTENTIAL OF APANTELES CREATONOTI VIERECK (HYMENOPTERA) IN RELATION TO AGE OF THIOCIDAS POSTICA WLK. CATERPILLARS (LEPIDOPTERA) - SATHE, T. V.; SANTHAKUMAR, M. V.; NAMDAR, S. A.; INGAWALE, D. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
Reproductive potential in relation to host age was studied providing 1 to 10 day old Thiocides postica Wik, larvae to Apanteles creatonoti Viereck. Age groups 2-9 day old were susceptible, 4 day old shows maximum 41.33% parasitism while I and 10 day old remained unparasitized. The study was conducted at laboratory conditions (24 - 1°C, 55 to 60%. R. H.),